Study on drug profile used in common pregnancy influenced issues and its complications - V., Semmalar G.; S. J., Kaviya Anisha; B., Terry Sheetal; T., Saravanakumar R.; K., Latha (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Pregnancy influenced issues are common among pregnant women treated by medications that causes complication in mother and fetus. The study aims to identify patients with pregnancy influenced issues like gestational diabetes mellitus, gestational hypertension, gastroesophageal reflux disease and anaemia. To assess the drug used pattern along with antibiotic therapy and to observe the above disease related complications. Methods: A hospital based prospective observational study was conducted at department of obstetrics and gynecology in Rajah Muthiah Medical College and Hospital. Totally 100 patients enrolled and data was collected using data collection form. Results: Out of 100 patients, high prevalence occurred in 26-30 years of age. Primarily gestational hypertension (39%), treated with Tab. Labetatol and complications were premature delivery, low birth weight. Anaemia (25%) cases treated with Tab. Ferrous sulphate, Iron sucrose and Folic Acid, Preterm delivery as complication. Gestational diabetes mellitus (18%) treated with Metformin and Human Insulin and complications were preterm delivery, maternal obesity, increased child weight. GERD (8%) treated with Pantoprazole, Ondansetron, Bifilac and complications were weight loss, dehydration, low birth weight. In pre-operative cases, 79% received antibiotics as monotherapy and 21% as dual therapy. In post-operative cases, 41% received antibiotics as monotherapy and 59% as dual therapy. Metronidazole (95%) given in both post and pre- operative conditions. Conclusions: The present study provides valuable insight about the overall drugs used in pregnancy related diseases and complications arise. We hope our data will make necessary recommendations to all health care professionals and pregnant women to ensure all pregnancy related safety measures were taken.